Perspectives among employees at Kemubu Agricultural Development Authority (KADA) Kota Bharu Kelantan towards knowledge sharing / Ahmad Fathul Hafiz Ahmad Zailani - Ahmad Zailani, Ahmad Fathul Hafiz (2016)
The present research investigates the perspectives of knowledge sharing on employees at Kemubu Agricultural Developmental Authority (KADA), Kota Bharu, Kelantan such as trust, formalization, knowledge technology, empowering leadership, effective reward system and motivation that revealed by most past researcher's studies. The data collected through questionnaire from 126 respondents. Questionnaire was dist1ibuted by using convenient sampling method. Reliability test, descriptive statistic, multiple regression and correlation were used to analyse the data through SPSS. This study limited to this organization only and the results may not applicable to other organization.